Analisis Distribusi Rumah Tangga Penerima Subsidi Listrik di Kabupaten Aceh Timur Tahun 2017 - Nur Shima; Samsul Anwar (Faculty of Economics and Business, Universitas Malikussaleh, 2017)
Act No. 30 of 2007 on Energy mandated the Government to provide electricity subsidy assistance to the poor. Based on data from BAPPEDA of East Aceh District, there are 6,932 Households (RT) enrolling the electricity subsidy program and only 45.99% are eligible to enjoy the program. East Aceh District Government conducted a rigorous selection process to the potential beneficiaries of this program. This study aims to determine whether there is a difference in the proportion of RT that receiving electricity subsidies per RT that have KKS (family cards prosperous) in East Aceh District. The statistical method used in this research was Analysis of Variance (Anova). Anova analysis shows that there is no difference in the proportion of households receiving electricity subsidies/ KKS beneficiaries among sub-district groups in East Aceh District (p-value=0,912). Number of RT receiving electricity subsidy per number of households with KKS is balanced and evenly distributed in each sub-district group in East Aceh District. So it can be concluded that the electricity subsidy program has been running successfully and justly.Keywords : Analysis of Variance (Anova), Electricity Subsidy Program, Households (RT), KKS (Family Cards Prosperous)